Do investment banks compete in IPOs?: the advent of the “7% plus contract” - Hansen, R (Journal of Financial Economics, 2001)
The large number of initial public offerings (IPOs) with a 7% spread suggests either that investment bankers collude to profit from 7% IPOs or that the 7% contract is an efficient innovation that better suits the IPO. My tests do not support the collusion theory. Low concentration and ease of entry characterize the IPO market. Moreover, the 7% spread is not abnormally profitable, nor has its use been diminished by public awareness of collusion allegations. In support of the efficient contract theory, banks compete in pricing 7% IPOs on the basis of reputation, placement service, and underpricing.